Evaluation of Health-Related Quality of Life in Patients with Type 2 Diabetes Mellitus through EQ-5D-3L: in public sector hospitals of Quetta, Pakistan - Haider Khan, Hamad; Khan, Faiz Ullah; Ahmad, Tawseef; Guo , Hui; Shi, Bingyin (Jordan Journal of Pharmaceutical Sciences, 2025)
Background: Diabetes mellitus (DM) is a chronic metabolic illness associated with substantial morbidity and mortality worldwide. It affects physical activity, social life, and mental health. In our country, most diabetes research has focused on morbidity and mortality. This study assessed the quality of life (QOL) of type 2 diabetes mellitus (DMT-2) patients in Quetta, Pakistan. Methods: This cross-sectional study examined 440 DMT-2 patients from public hospitals in Quetta between July and November 2021. The EuroQoL 5-Dimension 3-Level (EQ-5D-3L) scale was used to assess the health-related quality of life (HRQoL) of DMT-2 patients. Inferential statistical analyses were performed using SPSS version 22. Results: Most participants (73%) were aged between 35 and 55 years, with 246 (55.9%) males. The largest group of respondents (30.3%) had completed secondary school. Most patients (79.4%) reported no mobility issues, and 61.8% reported no difficulties with self-care. However, a substantial proportion (41.8%) experienced some difficulties with their usual activities. Additionally, 46.3% of patients reported moderate pain and discomfort. Significant correlations were found between HRQoL scores and gender (p=0.016), marital status (p=0.003), age (p=0.001), unemployment (p=0.001), and education (p=0.001). The time trade-off (TTO) and visual analog scale (VAS) scores were 0.496 and 0.555, respectively. Conclusion: The quality of life of DMT-2 patients depends on education, occupation, gender, and marital status. Therefore, these key factors influencing HRQoL should be prioritized when designing and implementing strategies to improve diabetes treatment and the quality of life of diabetic patients in this region.